2021
DOI: 10.1186/s12913-021-07133-5
|View full text |Cite
|
Sign up to set email alerts
|

“There’s a huge benefit just to know that someone cares:” a qualitative examination of rural veterans’ experiences with TelePain

Abstract: Background Veterans in the United States are at an increased risk of chronic pain and have higher reported pain prevalence and severity than nonveterans. This qualitative study aims to examine veterans’ perspectives on the acceptability of receiving pain care through TelePain, a telehealth program implemented by the Veterans Health Administration (VA) that offers specialty pain care to rural veterans in their homes or in a video conferencing room at a nearby outpatient clinic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated the integral role health coaching plays in patients achieving behavioral changes (24-27), and data show promising results for mental health, diabetes, heart disease, and general improvement of health and health-related quality of life (16,20,(28)(29)(30). Prior to COVID-19, most WH coaching was conducted face-to-face with little integration of video telehealth coaching.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the integral role health coaching plays in patients achieving behavioral changes (24-27), and data show promising results for mental health, diabetes, heart disease, and general improvement of health and health-related quality of life (16,20,(28)(29)(30). Prior to COVID-19, most WH coaching was conducted face-to-face with little integration of video telehealth coaching.…”
Section: Introductionmentioning
confidence: 99%
“…To address gaps in pain care in rural areas, the Veterans Health Administration (VA) is implementing a hub-andspoke telehealth model (Brecht et al, 2020), TelePain, to bring interdisciplinary pain care to sites that lack their own specialty pain management teams. Previously published literature has described the process for setting up a TelePain program (Glynn et al, 2021); observed increased access to pain care and increased use of telehealth for pain among rural patients following the implementation of TelePain (Chen et al, 2022); and documented patient satisfaction with the TelePain model of care (Silvestrini et al, 2021). In the VA TelePain model, a hub located at a major VA medical center hosts an interdisciplinary pain team that delivers multimodal, biopsychosocial pain service to spoke sites, which are rural community-based outpatient clinics and small VA facilities in the region.…”
Section: Introductionmentioning
confidence: 99%